2011
DOI: 10.1111/j.1751-7176.2010.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hypertension and Coronary Artery Disease as Assessed by Coronary Computed Tomography

Abstract: Multidetector row computed tomography (MDCT) enables the accurate noninvasive assessment of coronary artery stenosis and plaque imaging. The characteristics of patients who have coronary artery disease (CAD) as assessed by MDCT coronary computed tomography (CT) are not well known. Participants consisted of 513 consecutive patients with suspected CAD who underwent coronary CT. The authors quantified patient characteristics, including the prevalence of hypertension (HTN), hyperlipidemia and diabetes mellitus (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Computed tomography angiography (CTA) of the coronary arteries has been shown to clearly display the trunk and branches of the coronary arteries, particularly the trunk of the main coronary artery, the proximal segment of the right coronary artery, the proximal segment of the anterior descending branch, and the proximal segment of the left circumflex branch [10, 11]. CTA is less effective than CAG in displaying the distal segment of the right coronary artery, the distal segment of the left anterior descending branch, and the distal segment of the circumflex branch.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography angiography (CTA) of the coronary arteries has been shown to clearly display the trunk and branches of the coronary arteries, particularly the trunk of the main coronary artery, the proximal segment of the right coronary artery, the proximal segment of the anterior descending branch, and the proximal segment of the left circumflex branch [10, 11]. CTA is less effective than CAG in displaying the distal segment of the right coronary artery, the distal segment of the left anterior descending branch, and the distal segment of the circumflex branch.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was no significant contribution of increased waist circumference, increased fasting glucose, increased triglyceride, and decreased high-density-lipoprotein cholesterol ( Using data from a 3-year follow-up study in the workplace, increased blood pressure in men significantly contributed to the incidence of cerebrovascular ⁄ cardiovascular disease in concordance with reports by Mitsutake and associates. 1 In addition, there was no significant contribution of waist circumference on the incidence of cerebrovascular ⁄ cardiovascular disease as Mitsutake and coworkers 1 and Furukawa and colleagues 3 separately pointed out.…”
Section: Tomoyuki Kawada MDmentioning
confidence: 98%
“…Mitsutake and colleauges 1 conducted a cross‐sectional clinical study and concluded that hypertension is significantly associated with coronary artery disease (CAD) as assessed by coronary computed tomography (CT). They first recognized that age and the metabolic syndrome are both significantly associated with CAD, and then several metabolic components such as hypertension, dyslipidemia, diabetes, and visceral fat were used as independent variables to analyze the relationship with CAD.…”
mentioning
confidence: 99%
“…We evaluated coronary stenosis using CCTA as previously described [6][7][8][9][10][11]. Patients were assessed by 64-multidetector computed tomography (MDCT) on an Aquilion 64 (TOSHI-BA, Tokyo, Japan) or 320-MDCT on an Aquilion ONE Vi-SION (TOSHIBA, Tokyo, Japan).…”
Section: Evaluation Of Coronary Stenosis the Number Of Significantlymentioning
confidence: 99%
“…Thus, CACS is a good marker of future CVD risk. We have been studying the CCTA Registry at Fukuoka University in Japan (FU-CCTA Registry) and identified CVD risk factors for the primary prevention of CAD [6][7][8][9][10][11]. Using the FU-CCTA Registry, we determined the association between CACS and the prognosis in patients who underwent CCTA.…”
Section: Introductionmentioning
confidence: 99%